2019
DOI: 10.14710/jitaa.44.3.243-251
|View full text |Cite
|
Sign up to set email alerts
|

Exploring effects of betaine-homocysteine methyltransferase (BHMT) gene polymorphisms on fatty acid traits and cholesterol in sheep

Abstract: This study was aimed to explore the effects of Betaine-Homocysteine Methyltransferase (BHMT) gene polymorphisms on fatty acid traits and cholesterol in lambs. This study used a total of 147 blood samples for genotyping including 19 Javanese Fat-Tailed (JFT), 16 Javanese Thin-Tailed (JTT), 41 Composite Garut (CG), 35 Compass Agrinak (CA) and 36 Barbados Black Belly Cross (BC). A total of 61 rams as representative from five breed of sheep were selected for association study. Identification of BHMT single nucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 15 publications
4
12
1
Order By: Relevance
“…Overall, the result showed the average value of SFA in lamb meat was higher than UFA (PUFA+MUFA) in all genotypes. This result agrees with the current study by Munyaneza et al (2019) that generally fatty composition of lamb meat is dominated by SFA. MUFA could reduce LDL cholesterol (low-density lipoprotein) and increase HDL cholesterol (high-density lipoprotein) levels.…”
Section: Discussionsupporting
confidence: 94%
“…Overall, the result showed the average value of SFA in lamb meat was higher than UFA (PUFA+MUFA) in all genotypes. This result agrees with the current study by Munyaneza et al (2019) that generally fatty composition of lamb meat is dominated by SFA. MUFA could reduce LDL cholesterol (low-density lipoprotein) and increase HDL cholesterol (high-density lipoprotein) levels.…”
Section: Discussionsupporting
confidence: 94%
“…The TT genotype was relatively rare in the populations (JFT, JTT, BCS, CAS, GS, and JS). This finding is similar to an association study which has used a different gene (diacylglycerol O-acyltransferase 1 [DGAT1]) in JFT, JTT, BCS, CAS, and GCS [27], however it is inconsistent with the previous study performed for a different gene (betaine-homocysteine S-methyltransferase [BHMT]) in JFT, JTT, BCS, CAS, and GCS [28]. Munyaneza et al [28] reported that TT genotypes are more frequent than CC and CT genotypes.…”
Section: Discussionsupporting
confidence: 47%
“…The HSD17β13 gene of SNP g.101 689 913 C>T had no significant association with flavor and odor (Table 5). In Indonesian lamb quality, several genes that affected flavor odor and fatty acid composition were APOA5 (Gunawan et al, 2018), CYP2A6 (Listyarini et al, 2018), BHMT (Munyaneza et al, 2019), and CYP2E1 (Harahap et al, 2020).…”
Section: Association With Flavor Odor and Fatty Acid Compositionmentioning
confidence: 99%